As pragmatic as theft over honest toil: Disentangling pragmatism From operationalism - Maul, A; McGrane, J (Taylor and Francis, 2017)
The concept of pragmatism has come to garner widespread appeal over the past century, particularly in the context of methodological innovations in the social and psychological sciences. In addition to connoting an orientation towards practicality and real-world usefulness—and who among us would not want to claim such things—pragmatism is often used to suggest freedom from slavish devotion to abstract principles or theoretical concerns. The assumption of this freedom has led to a diversification of activities being referred to as measurement across different scientific disciplines and other areas of human activity. Many of these activities bear little resemblance to canonical instances of measurement in the physical sciences (e.g., the measurement of length, or temperature). Pragmatism, then, may seem to offer an alternative method of justification for the dependability and usefulness of the knowledge acquired as a result of these more liberally-defined measurement activities.